66.0k views
5 votes
What is the result of adding these two equations?

5x−9y=1−7x+2y=−5\begin{aligned} 5x-9y &= 1 \\\\ -7x+2y &= -5 \end{aligned}

5x−9y


−7x+2y




=1

=−5



User Eren Golge
by
5.2k points

2 Answers

0 votes

Answer:

-2x - 7y = -4

~

What is the result of adding these two equations?
5x - 9y = 1

-7x + 2y = -5

User Willis Hershey
by
4.6k points
2 votes

Answer:

-2x-7y=-4

Explanation:

We want to add the two expressions


\begin{aligned} 5x-9y &= 1 \\ -7x+2y &= -5 \end{aligned}

First we add the Left Hand Sides and do the same to the Right Hand Sides. This gives us:

(5x-9y)+(-7x+2y)= 1 +( -5)

Open the brackets

5x-9y-7x+2y=1-5

Regroup like terms

5x-7x-9y+2y=-4

-2x-7y=-4

The result of adding the two given expressions is -2x-7y=-4.

User Earlyn
by
5.3k points